Effect of hygroscopic growth on the aerosol light-scattering coefficient: A review of measurements, techniques and error sources. (September 2016) - Titos, G.; Cazorla, A.; Zieger, P.; Andrews, E.; Lyamani, H.; Granados-Muñoz, M.J.; Olmo, F.J.; Alados-Arboledas, L.
Abstract: Knowledge of the scattering enhancement factor, f (RH), is important for an accurate description of direct aerosol radiative forcing. This factor is defined as the ratio between the scattering coefficient at enhanced relative humidity, RH, to a reference (dry) scattering coefficient. Here, we review the different experimental designs used to measure the scattering coefficient at dry and humidified conditions as well as the procedures followed to analyze the measurements. Several empirical parameterizations for the relationship between f (RH) and RH have been proposed in the literature. These parameterizations have been reviewed and tested using experimental data representative of different hygroscopic growth behavior and a new parameterization is presented. The potential sources of error in f (RH) are discussed. A Monte Carlo method is used to investigate the overall measurement uncertainty, which is found to be around 20–40% for moderately hygroscopic aerosols. The main factors contributing to this uncertainty are the uncertainty in RH measurement, the dry reference state and the nephelometer uncertainty. A literature survey of nephelometry-based f (RH) measurements is presented as a function of aerosol type. In general, the highest f( RH) values were measured in clean marine environments, with pollution having a major influence on f( RH). Dust aerosol tended to have the lowest reported hygroscopicity of any of the aerosol types studied. Major open questions and suggestions for future research priorities are outlined. Highlights: Uncertainty in f (RH) is 20–40% for moderately hygroscopic aerosols. Assumption of no growth at RH<40% contribute to higher uncertainty. High variability in measured f (RH) values. Highest f (RH) values in clean marine environments.